An ecological framework for contextualizing carnivore–livestock conflict. Issue 4 (14th May 2020) - Wilkinson, Christine E.; McInturff, Alex; Miller, Jennifer R. B.; Yovovich, Veronica; Gaynor, Kaitlyn M.; Calhoun, Kendall; Karandikar, Harshad; Martin, Jeff Vance; Parker‐Shames, Phoebe; Shawler, Avery; Van Scoyoc, Amy; Brashares, Justin S.
Abstract: Carnivore predation on livestock is a complex management and policy challenge, yet it is also intrinsically an ecological interaction between predators and prey. Human–wildlife interactions occur in socioecological systems in which human and environmental processes are closely linked. However, underlying human–wildlife conflict and key to unpacking its complexity are concrete and identifiable ecological mechanisms that lead to predation events. To better understand how ecological theory accords with interactions between wild predators and domestic prey, we developed a framework to describe ecological drivers of predation on livestock. We based this framework on foundational ecological theory and current research on interactions between predators and domestic prey. We used this framework to examine ecological mechanisms (e.g., density‐mediated effects, behaviorally mediated effects, and optimal foraging theory) through which specific management interventions operate, and we analyzed the ecological determinants of failure and success of management interventions in 3 case studies: snow leopards ( Panthera uncia ), wolves ( Canis lupus ), and cougars ( Puma concolor ). The varied, context‐dependent successes and failures of the management interventions in these case studies demonstrated the utility of using an ecological framework to ground research and management of carnivore–livestock conflict. Mitigation of human–wildlife conflict appears to require an understanding of how fundamental ecological theories work within domestic predator–prey systems. Abstract : Article impact statement : Applying long‐established ecological concepts to human‐managed systems can inform more effective management of carnivore–livestock conflict. Abstract : Un Marco de Trabajo Ecológico para Contextualizar el Conflicto Carnívoro – Ganado Resumen: La depredación del ganado por carnívoros es un reto complejo para el manejo y las políticas, a pesar de que es intrínsecamente una interacción ecológica entre depredadores y presas. Las interacciones entre humanos y la fauna ocurren en sistemas socio‐ecológicos en los que los humanos y los procesos ambientales están conectados estrechamente. Sin embargo, el conflicto humano – fauna subyacente y la clave para desenredar su complejidad son mecanismos ecológicos complejos e identificables que resultan en eventos de depredación. Para tener un mejor entendimiento sobre cómo la teoría ecológica armoniza con las interacciones entre los depredadores silvestres y la presa doméstica, desarrollamos un marco de trabajo para describir las causantes ecológicas de la depredación del ganado. Basamos este marco de trabajo en las principales teorías ecológicas y las investigaciones actuales sobre las interacciones entre los depredadores y las presas domésticas. Usamos este marco de trabajo para examinar los mecanismos ecológicos (es decir, los efectos mediados por la densidad, los efectos mediados por el comportamiento, y la teoría del forrajeo óptimo) mediante los cuales operan ciertas intervenciones específicas de manejo y analizamos las determinantes ecológicas del fracaso y el éxito de las intervenciones de manejo en tres estudios de caso: el leopardo de las nieves ( Panthera uncia ), el lobo ( Canis lupus ), y el puma ( Puma concolor ). Los éxitos y fracasos variados y dependientes del contexto que sufrieron las intervenciones de manejo en estos estudios de caso demostraron la utilidad del uso de un marco de trabajo ecológico para aterrizar la investigación y el manejo del conflicto carnívoro ‐ ganado. La mitigación del conflicto humano – fauna parece requerir de un entendimiento sobre cómo funcionan las teorías ecológicas fundamentales dentro del sistema doméstico depredador – presa. 摘要: 食肉动物对家畜的捕食是管理和政策上面临的一项复杂挑战, 但它本质上也是捕食者和猎物的生态互作问题。人兽互作发生在人类与环境过程紧密联系的社会生态系统中; 然而, 人兽冲突及揭示其复杂性的本质则是导致捕食事件发生的、具体明确的生态学机制。为了更好地理解生态学理论如何反映野生捕食者和家养猎物之间的互作, 我们开发了一个框架来描述捕食家畜的生态驱动力。这个框架基于基础生态学理论和捕食者与家养猎物互作的研究现状。我们用这个框架分析了采取特定管理干预措施所依赖的生态学机制 (如密度调控作用、行为调控作用和最优觅食理论), 并对决定管理干预成败与否的生态学因素进行了三个案例分析, 分别涉及雪豹 ( Panthera uncia ) 、灰狼 ( Canis lupus ) 和美洲狮 ( Puma concolor ) 。这些案例中管理干预的成败取决于具体情境, 这显示了我们的生态框架在开展食肉动物与家畜冲突的研究和管理中的有效性。我们认为, 减缓人兽冲突需要了解基础生态学理论在捕食者‐家养猎物系统中的作用原理。 【翻译: 胡怡思; 审校: 聂永刚】